Impact of in-hospital birth weight loss on short and medium term breastfeeding outcomes - Sergio Verd; Diego de Sotto; Consuelo Fernández; Antonio Gutiérrez (BMC, 2018)
Abstract Background The definition for lower limit of safe birthweight loss among exclusively breastfed neonates is arbitrary. Despite this, in cases of great in-hospital weight loss, breastfeeding adequacy is immediately questioned. The aim of this study was to examine the relationship between weight loss at discharge from hospital, when babies are ready to go home, and eventual cessation of exclusive breastfeeding since birth. Methods This is a secondary analysis of a cohort study. Study participants were 788 full term, breastfed and stable babies, born in 2007-2012 consecutively enrolled to primary care pediatric clinics in Majorca, Spain. Data were collected by chart review. The main predictor was birthweight loss at discharge. Extreme weight loss was defined as the 90th and 95th centiles of birthweight loss for babies who were delivered by vaginal delivery and by cesarean section. Main outcomes were cessation of exclusive breastfeeding by 7, 15, 30 and 100 days of life. Multivariate regression analysis was performed to study the relationship of selected variables with exclusive breastfeeding cessation since birth. Results We observed a median weight loss of 6%. In bivariate analysis, quartiles of birthweight loss at discharge were predictive of exclusive breastfeeding cessation at 15, 30 and 100 days postpartum. In multivariate analysis: in-hospital weight loss above the median did predict exclusive breastfeeding cessation by 15, 30 and 100 days of life, Adjusted Odds Ratios (AORs) (95% Confidence Intervals [CIs]): 1.57 (1.12, 2.19), 1.73 (1.26, 2.38) and 1.69 (1.25, 2.29), respectively. In contrast, we did not find that newborn extreme weight losses were associated with exclusive breastfeeding cessation. Conclusions We report that extreme birthweight loss does not trigger immediate formula supplementation. We do not identify any cut-off values to be used as predictors for the initiation of supplementary feeding, this research question remains unanswered.